Ethnic background and youth unemployment in Germany - Michael Zibrowius (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2013)
The empirical literature has shown on numerous occasions that immigrants and their offspring fare worse economically than natives with comparable observable characteristics. This study addresses youth unemployment as an important determinant of youths' later labor market success by looking at the determinants of the hazard of first unemployment after age 17, when compulsory schooling is over. Proportional hazard models show no evidence for a statistically significantly higher risk of becoming unemployed for both first and second generation immigrants compared to natives. However, further differentiating by ethnic background, hazard rates are significantly higher for individuals with Turkish origin compared to Germans, ceteris paribus. These differences vanish only party when controlling for individual, family, and regional characteristics, they differ by gender and immigrant generation, and they are particularly strong for longer unemployment spells.
Keywords: J61; J64; J71; 330; immigrants; labor market entry; youth unemployment; survival time